From the cradle to the grave: Green turtle hatchlings (Chelonia mydas) preyed upon by two-spots red snappers (Lutjanus bohar) - Juhel, Jean-Baptiste; Maire, Eva; Sucré, Elliott; Cheutin, Marie-Charlotte; Marques, Virginie; Benkwitt, Cassandra; Gunn, Rachel L.; Richards, Eilísh; Albouy, Camille (Food webs, 2019)
The observation of trophic interactions such as predation provide valuable information to model food webs and better understand ecosystem functioning. Such information is crucial for rare and endangered species in order to adapt management measures and ensure their conservation. However, trophic interactions are rarely observed in the marine realm, even for well-known or widespread species. During a scientific cruise in the Scattered Islands (Southwestern Indian Ocean), we observed endangered green turtle hatchlings (Chelonia mydas) in the gut content of two subadults two-spots red snappers (Lutjanus bohar). This trophic link involving emblematic species has not been previously described. The two-spots red snapper is a widespread coral reef fish in the tropical Indo-Pacific. Although it is unclear how fish predation affects marine turtle population dynamics, the occurrence of hatchlings in all the snapper samples suggests that fish could be significant sources of predation. Yet this predation pressure remains to be further studied and quantified to be considered in marine turtle population monitoring.